2017
DOI: 10.1140/epjb/e2017-80071-2
|View full text |Cite
|
Sign up to set email alerts
|

Luttinger theorem and imbalanced Fermi systems

Abstract: Abstract. The proof of the Luttinger theorem, which was originally given for a normal Fermi liquid with equal spin populations formally described by the exact many-body theory at zero temperature, is here extended to an approximate theory given in terms of a "conserving" approximation also with spin imbalanced populations. The need for this extended proof, whose underlying assumptions are here spelled out in detail, stems from the recent interest in superfluid trapped Fermi atoms with attractive inter-particle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Quantum phase transitions are associated with the change in the number of Fermi surfaces when the system parameters are varied. In a recent article [85], the validity of the Luttinger's theorem was proven for any approximate theory based on a conserving approximation in case of spindensity imbalance. In the FFLO state, pairing occurs in such a way that the minority Fermi surface can be thought of as shifted by the FFLO wave vector q.…”
Section: 10luttinger's Theorem and Fermi Surfacesmentioning
confidence: 99%
“…Quantum phase transitions are associated with the change in the number of Fermi surfaces when the system parameters are varied. In a recent article [85], the validity of the Luttinger's theorem was proven for any approximate theory based on a conserving approximation in case of spindensity imbalance. In the FFLO state, pairing occurs in such a way that the minority Fermi surface can be thought of as shifted by the FFLO wave vector q.…”
Section: 10luttinger's Theorem and Fermi Surfacesmentioning
confidence: 99%
“…These methods were applied to study the finite temperature BCS-BEC crossover, in particular the phase diagram of non-polarized [43,44] and polarized [45] gases. In [46], it was shown that within the Luttinger-Ward formalism, the Luttinger theorem is exactly fulfilled with the full Dyson equation.…”
Section: Discussionmentioning
confidence: 99%